(NfIZIKA (B:s (NpROBLEMY(B, (NISTORIQ(B, (NL@DI (B: (NsBORNIK NAU^NYH TRUDOW (B/s - (NtU^KEWI^(B, (NwLADIMIR mAKSIMOWI^s; (NfIZIKO(B-(NTEHNI^ESKIJ IN(B-(NT IM(B. (Na(B.(Nf(B. (NiOFFEs ((Nl(B. :s (NnAUKA(B. (NlENINGR(B. (NOTD(B-(NNIE(B,s, 1986)
(NbIBLIOGR(B. (NW KONCE ST(B.s
(NfIZIKO(B-(NTEHNI^ESKIJ IN(B-(NT IM(B. (Na(B.(Nf(B. (NiOFFEs
Keywords: (NfIZIKAs